Pragmatics of Communication and Neo-Sophists: Models of Theatrical Oratory - Lo Verde, Chiara (2019)
The biographer Flavius Philostratus (II-III AD), in his work Lives of the Sophists, coins the expression “Second Sophistic” to depict new outlooks and new trends in Greek oratory, focusing mostly on the II century AD. The perspective of his narration is quite clear: the performative aspects of declamations and the behavioral elements of sophists. Contemporary studies about pragmatics of communication can provide us with lens with which to read these biographies. Histrionic and theatrical characters, such as Scopelian from Clazomenae and Polemo of Laodicea, with their dramatic performances and self-presentations, let us analyze the sequence of interactions during the “ritual game” between the public and the orators. The analogic communication is to a large extent entrusted to non-verbal traits, like gestures, glance, face expressions and deportment. To avoid a dysfunctional relation between the speaker and listeners/spectators, especially in a so-called ‘face to face society’, accurate knowledge of the rules of the ‘social contact’ is required.
Keywords: pragmatics; communication; rhetoric; second sophistic; body language; interaction; public; performance budget; oratory; sophist; behavior; character; biography; social; deportment; strategies; dramatic